Analysis of Islamic Business Ethics Related to Return of Remaining Prices in Kind (Case Study of Taraju Tasikmalaya Market) - Ranti Ismayanti (QISTINA: Jurnal Multidisiplin Indonesia, 2022)
The problem in this study is the Return of Remaining Prices in the Form of Goods at the Tasikmalaya Taraju Market and what are the factors causing the practice. This study "aims to find out clearly how the practice of residual returns in the form of goods according to the perspective of Islamic business ethics and what factors cause the remaining prices to be returned in the form of commodities in the Taraju Tasikmalaya market. The type of research used in this thesis uses the qualitative approach method of phenomenological research. The data sources used in this study are primary data in the form of observations, documentation, and interviews with dealers and buyers who have experienced this as in secondary data. The results of the research conducted at Tasikmalaya Taraju Market are in accordance with Islamic business ethics, which is legal or permissible as long as the parties do not feel disadvantaged because of it and both parties are mutually aware of the transaction. The seller first asks the buyer before the practice is carried out, sometimes the buyer's desire is also the return of the remaining price in place of the goods." because the seller first tells consumers what are the factors in the practice, namely the limitation of dimes, the buyer's own desire for change to be exchanged for goods, and to streamline the transaction time, because if there is no dime, the seller must first exchange  the money goes to the other sellers of course" it will take a lot of time.